Sistem Informasi Manajemen Hotel Berbasis Web - Yosita Lianawati; Diwahana Mutiara Candrasari Hermanto (Media Aplikom, 2022)
The development of advances in information technology requires business people to use this technology, but there are still many hotels that use manual systems for data handling and recording. The Hotel Management Information System was made using the interview method, literature study, and observation to the location for data collection. This research will be designed using the PHP programming language and MySQL database. From the results of this study, it has been proven that the Hotel Management Information System can help hotels to improve efficiency and effectiveness in the booking process, data processing and produce information quickly and accurately.